2012
DOI: 10.2527/jas.2011-4403
|View full text |Cite
|
Sign up to set email alerts
|

Amount and source of dietary copper affects small intestine morphology, duodenal lipid peroxidation, hepatic oxidative stress,and mRNA expression of hepatic copper regulatory proteins in weanling pigs1,2

Abstract: Thirty weanling, crossbred barrows (SUS SCROFA) were used to determine the effects of amount and source of dietary Cu on small intestinal morphology and lipid peroxidation, Cu metabolism, and mRNA expression of proteins involved in hepatic Cu homeostasis. At 21 d of age, pigs were stratified by BW (6.33 ± 0.23 kg) and allocated to 1 of the following dietary treatments: i) control (no supplemental Cu; 6.7 mg Cu/kg), ii) 225 mg supplemental Cu/kg diet from Cu sulfate (CuSO(4)), or iii) 225 mg supplemental Cu/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
56
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 23 publications
(26 reference statements)
11
56
2
3
Order By: Relevance
“…Plants need Cu for the production of chlorophyll and proteins and for various biochemical processes. Concentrations of Cu in our study were toxic and lethal [56]. Symptoms of Cu toxicity include liver and kidney damage, nausea, and diarrhea.…”
Section: Copper (Cu)mentioning
confidence: 60%
“…Plants need Cu for the production of chlorophyll and proteins and for various biochemical processes. Concentrations of Cu in our study were toxic and lethal [56]. Symptoms of Cu toxicity include liver and kidney damage, nausea, and diarrhea.…”
Section: Copper (Cu)mentioning
confidence: 60%
“…Estos resultados coinciden con Fry et al (2012), quienes encontraron una disminución en la altura de vellosidad a nivel del duodeno y yeyuno proximal a una suplementación de 225 ppm de cobre en la dieta de cerdos destetados. Este autor señala que el cobre puede actuar como agente prooxidante y estar involucrado en la oxidación de los lípidos y el estrés oxidativo sobre las membranas celulares.…”
Section: Resultados Y Discusiónunclassified
“…A nivel hepático, la concentración de este mineral se incrementa conforme aumentan los nivel farmacológicos de cobre en la dieta, encontrándose diferencia estadística significativa entre todos los tratamientos (p<0.05). Estos resultados son similares a los obtenidos en cerdos (Fry et al, 2012) (1961), estudiando el proceso de absorción, distribución y excreción de cobre con isótopos marcados, encontraron que cerdos suministrados con 24 ppm de Cu en la dieta tuvieron un nivel de absorción de 8.7%, pero cuando se le suministró 185 ppm de Cu se redujo a 2.9% el nivel de absorción, lo cual demostró que la absorción de cobre es menor del 10% cuando es suplementado a niveles farmacológicos en la dieta de cerdos.…”
Section: Resultados Y Discusiónunclassified
“…The degree of lipid peroxidation could be evaluated by MDA [27]. Reports about the effects of pharmacological Cu in feed on tissue MDA concentrations focused on the duodenum rather than the serum and liver [16,28]. A previous study showed that duodenal MDA contents were higher when pigs were fed 225 mg/kg supplemental Cu as CuSO4 rather than TBCC [16].…”
Section: Discussionmentioning
confidence: 99%